Health Center staff, 1965 - Billy Mounts, M.D.::::::::: (1965)
1965 Health Center staff. (left to right) Back row: Don Curtis, lab; Donna Porter, clerk; Irene Shrode, RN; Mary Jo Summers, RN; Liz Dye, physiotherapist; Eugene Wiggenhorn, pharmacist; Vi Hughes, secretary; Barbara Hammonds, lab; Everett Chandler, Dean of Students. Middle row: Fern Graham, aide; Lois Larsen, RN; Rhoda Downing, X-ray; Leona Hansen, chef; Art James, MD. Front Row: Loretta Forrest, aide; ____, RN; Madge Jacks, MD; Imogene Gow, RN; Billy Mounts, MD; Pat Ellers, RN; Ruth Gran, RN; Florence Messler, Rn; Lloyd Hennig, MD.